골프장의 재무특성이 회원권 가치에 미치는 영향 - 모현숙; Hyun Sook Mo; 이학동; Hak Dong Lee (감정평가학 논집, 2012)
골프장의 회원권 가치가 어떤 요인에 영향을 받는지는 다수의 연구자가 밝혔다. 그동안 규명한 주요내용은 골프장의 접근성과 부킹횟수 등이 회원권의 가치에 영향을 미친다는 것이다. 본 연구는 주로 재무특성 요인들이 회원권 가치에 영향을 주는지 분석한 것이며, 분석결과는 다음과 같다. 회원권 가치에 영향을 미친 요인은 홀수, 회원1인당 홀수, 그리고, 재무특성요인인 골프장시가총액,1인당 입회금, 입회금비율 5개 변수들이 유의미하게 나타났다. 9개의 요인 중 3개의 재무특성 변수들이 영향을 미치는 것으로 분석되어 재무특성이 회원권 가치에 영향을 미치는 것을 규명하였다. 특히, 회원권 가치결정에서 입회금비율은 골프장의 재무를 나타내는 지표로서 회원권가격에 강력하게 부의 영향을 미치는 것으로 나타났다. 입회금비율이 높으면 골프장의 부채가 증가하기 때문에 회원권 가치가 하락하며, 부채가 골프장 시가총액을 초과하게 된다. 이것은 골프장 재무상태가 불안정한 것을 시사하므로 회원권 보유자는 환불요청을 하거나 골프장을 저평가하는 원인이 된다. 골프장의 재무특성 요인들은 골프장이 관심을 갖고 관리해야 하는 변수임을 알 수 있다. The factors affect a golf membership value have been discussed by many precedent studies. The main findings from the precedent studies are that the accessibility and a number of bookings affect a golf membership value. This study mainly focuses on identifying and analyzing if the financial characteristics affect a golf membership value and the findings are as follows. A number of holes, a number of holes per capita, area per capita and the financial factors such as total market value, initial deposit per capita and an initial deposit ratio appeared to be significant factors. As three of nine are financial factors that affect the golf membership value, the financial characteristics are identified as distinctive factors. Especially, the initial deposit ratio is a financial indicator in valuation of golf membership and it is in a strong inverse relationship with the golf membership value. Because the debt to the golf club increases when the initial deposit ratio is high, the debt would exceed the total market value if the golf membership value decreases. This implies that the financial status of the golf club is unstable and the membership holders may eventually request for a refund or it can be a cause for the undervaluation of the golf club. Thus, the financial characteristics are variables that they should be advertently managed.